PSMA-targeting iron oxide magnetic nanoparticles enhance MRI of preclinical prostate cancer. (February 2015) - Tse, Brian Wan-Chi; Cowin, Gary J; Soekmadji, Carolina; Jovanovic, Lidija; Vasireddy, Raja S; Ling, Ming-Tat; Khatri, Aparajita; Liu, Tianqing; Thierry, Benjamin; Russell, Pamela J
Aim: To evaluate the potential of newly-developed, biocompatible iron oxide magnetic nanoparticles (MNPs) conjugated with J591, an antibody to an extracellular epitope of PSMA, to enhance MRI of prostate cancer.Materials & methods: Specific binding to PSMA by J591-MNP was investigated in vitro . MRI studies were performed on orthotopic tumor-bearing NOD.SCID mice 2 h and 24 h after intravenous injection of J591-MNPs, or non-targeting MNPs.Results & conclusion : In vitro, MNPs did not affect prostate cancer cell viability, and conjugation to J591 did not compromise antibody specificity and enhanced cellular iron uptake. Magnetic resonance contrast of tumors was increased in vivo using PSMA-targeting MNPs, but not by non-targeting MNPs. This provides proof-of-concept that PSMA-targeting MNPs have potential to enhance magnetic resonance detection/localization of prostate cancer.